THE DISMISSAL OF FAMILY POWER AND PERSONALITY RIGHTS (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2023)
The research aims to analyze the exercise of family power, the action of dismissal and its correlation with personality rights. In order to reach this objective, the evolution through which the family power institute has passed will be analyzed, as well as the causes of dismissal provided for in the law, from the point of view of personality rights. Through the hypothetical-deductive method, with research in doctrine and jurisprudence, it will be verified that the action of removal of family power is an instrument for the realization of personality rights, taking into account the right to family life and above all the principle of dignity of the human person.